2016
DOI: 10.1016/j.jcot.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency among pediatric osteoarticular tuberculosis patients

Abstract: The osteoarticular tuberculosis cases had low serum vitamin D levels compared to healthy controls. The low vitamin D levels were persistent irrespective of gender and age in osteoarticular tuberculosis children. There was widespread vitamin D insufficiency in apparently healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…An observational study conducted to assess the serum concentration of 25(OH)D among children with active tuberculosis (TB) using non-TB pneumonia and healthy controls revealed that larger number of vitamin D deficient children were from active TB group [ 9 ]. Similarly, many studies conducted elsewhere [ [10] , [11] , [12] , [13] , [14] ] delineated similar findings including Dabla's study conducted among pediatric osteoarticular tuberculosis patients which revealed that 56% of active TB cases were vitamin D deficient and had lower levels of serum 25(OH)D compared to healthy controls [ 11 ]. However, significant number of studies found no significant difference in vitamin D deficiency status TB patients and healthy children [ [15] , [16] , [17] ].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…An observational study conducted to assess the serum concentration of 25(OH)D among children with active tuberculosis (TB) using non-TB pneumonia and healthy controls revealed that larger number of vitamin D deficient children were from active TB group [ 9 ]. Similarly, many studies conducted elsewhere [ [10] , [11] , [12] , [13] , [14] ] delineated similar findings including Dabla's study conducted among pediatric osteoarticular tuberculosis patients which revealed that 56% of active TB cases were vitamin D deficient and had lower levels of serum 25(OH)D compared to healthy controls [ 11 ]. However, significant number of studies found no significant difference in vitamin D deficiency status TB patients and healthy children [ [15] , [16] , [17] ].…”
Section: Introductionsupporting
confidence: 56%
“…Different studies among under five children shows that decreased level of 25(OH)D were more prevalent among under five children with respiratory tract infections (RTIs) and its deficiency was associated with increased risk of RTIs [ [8] , [9] , [10] ]. Furthermore, studies also shows that, normal to high serum 25(OH)D status appears to have some beneficial influence on the incidence and severity of some, though not all, types of infections [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to prior studies that have reported articular involvement predominantly in the context of immunosuppression (Pigrau-Serrallach 2013, Calle 2018, Hodkinson 2009). Vitamin D deficiency has been associated with the osteoarticular TB, predominantly among paediatric patients (Dabla 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In India, three studies investigated serum 25(OH)D concentrations in children with osteoarticular TB [37,38] and intrathoracic TB [39]. Agarwal's study revealed hypovitaminosis D in 86% of patients while not discovering any discernible difference in 25(OH)D levels with respect to sex, age, or site of infection.…”
Section: Vitamin D and Tuberculosismentioning
confidence: 99%